Propagation Loss Determination of GSM Signal Strength in Selected Buildings in Ilorin, Nigeria - Akanni, J.; Oraiye, O. T.; Isa, A. A.; Ogunbiyi, O. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2021)
GSM signal building penetration loss is a problem often encountered by subscribers inside a building. As a result of building penetration loss, poor reception and signal outages often occur in many indoor locations and this accounts for increased attenuation of received signal strength of a cellular network signal when a subscriber with a mobile phone moves from outdoor to indoor. The study assessed the GSM signal penetration loss in thatched, wooden, block, mud and zinc buildings. Three network providers named A, B and C was used for the experiment. A low budget but very effective equipment (Two Tecno Pouvoir 3 plus Android phone) was used as the measurement tool. It was loaded with Network Signal Info application developed by KAIBITS Software GmbH installed software and positioned inside and outside the building to record indoor and outdoor GSM signal strength respectively for the three service providers in Ilorin, Nigeria. The results were then analyzed in order to determine and compare the path loss introduced by each of the selected buildings. This process was repeated for all the selected buildings, and the measurement was carried out for 6 months. The findings revealed that the outdoor signal strength was higher than the indoor signal strength for all the selected buildings; it also revealed that penetration loss is likely to be a function of the material used in the construction of the buildings. Zinc building has the highest penetration loss of 12.0dBm and thatched building has the least penetration loss of 2.6dBm. Information from this research will assist in selection of building materials for good indoor cellular network signal reception. It will also assist cellular network service providers in the link budget preparation for environments where similar building materials are used.